2011
DOI: 10.1002/hed.21419
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of epidermal growth factor receptor and insulin‐like growth factor receptor I: Reduction of angiogenesis and tumor growth in cutaneous squamous cell carcinoma

Abstract: Purpose-Cutaneous squamous cell carcinoma (CSCC) is the second most common nonmelanoma skin cancer. The majority of the ~250,000 cases occurring annually in the United States are small, non-aggressive, and cured by excision alone. However, a subset of these tumors which are defined by poorly differentiated histology, large tumor size, invasion of adjacent structures and/or regional metastases can prove resistant to treatment despite adjuvant radiotherapy and have increased risk of recurrence and nodal metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 66 publications
5
47
0
Order By: Relevance
“…11 Finally, various preclinical studies have shown improved activity when both IGF1R and EGFR are inhibited concomitantly. 12,13 Given that anti-IGF1R and anti-EGFR antibodies have shown toxicity clinically, it is important to study the combined effects of anti-IGF1R and anti-EGFR treatment quantitatively. Of particular interest is the hypothesis that subtoxic doses of each agent might yield efficacy comparable to that seen with toxic doses separately because of synergism when tested in combination.…”
Section: Resultsmentioning
confidence: 99%
“…11 Finally, various preclinical studies have shown improved activity when both IGF1R and EGFR are inhibited concomitantly. 12,13 Given that anti-IGF1R and anti-EGFR antibodies have shown toxicity clinically, it is important to study the combined effects of anti-IGF1R and anti-EGFR treatment quantitatively. Of particular interest is the hypothesis that subtoxic doses of each agent might yield efficacy comparable to that seen with toxic doses separately because of synergism when tested in combination.…”
Section: Resultsmentioning
confidence: 99%
“…All receptors of the ErbB family activate and regulate diverse cellular processes, including proliferation, survival, adhesion, migration and differentiation (1). Ligand binding potentiates receptor interaction with either a homologous molecule (homodimerization), a different ErbB-family receptor, or another cell surface tyrosine kinase receptor (IGF-1R or c-Met) (heterodimerization) (2)(3)(4)(5). Dimer formation causes autophosphorylation of a tyrosine residue in the cytoplasmic domain and activates proteins triggering downstream events.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR tyrosine kinase inhibitors (TKI) can induce EGFR/IGF-1R heterodimerization and alter the interactions between IGF-1R and insulin receptor (INSR) substrate (IRS)-1 in cancer cells, activating downstream signaling and resulting in resistance to further TKI treatment (34)(35)(36). Conversely, coinhibition of both pathways results in synergistic antitumor effects in several preclinical cancer models (36)(37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%